STRATEGI KOMUNIKASI DALAM PENGEMBANGAN OBYEK WISATA PANTAI MANDALA RIA DI KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
Tourism marketing communication is an increase in visit requests, also intended to create interaction or exchange of information between the organization and prospective tourists based on quality and satisfaction with the exchange process. The communication strategy is an effort made by the Tourism Office of the Regency of Bulukumba to be directly involved in the process of developing tourism objects, which is in the Mandala Ria Beach of Bulukumba Regency in order to further increase the attractiveness for the tourists. The purpose of this study was to determine the potential of the socio-cultural of the community in developing Mandala Ria beach. To find out opportunities and challenges in developing the beach attractions of Mandala Ria Ara-Lembanna, and to find out the communication strategy carried out by the Bulukumba Tourism Office in developing the potential of the Mandala Ria Ara-Lembanna Beach tourism object.